Development of LUPAS Media (LUDO IPAS) to Improve Students' Creative Thinking Skills in Elementary Schools - Kheisha Karisma Putri Anggayana; Habudin Habudin; Juhji Juhji (Al-Qalam Institute, 2025)
Creative thinking is an essential skill in 21st-century learning, yet many students still face difficulties in developing fluency, flexibility, elaboration, and originality. This study aims to develop a game-based learning medium called LUPAS (Ludo IPAS) to address these challenges in the topic of continents and countries. The research employed the ADDIE model, covering the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection through interviews and observations identified students’ learning needs, which became the basis for designing the LUPAS media. Expert validation showed high feasibility, with scores of 93.3% from material experts and 90.6% from media experts, both categorized as “very valid.” Implementation used a one-group pretest-posttest pre-experimental design with sixth-grade students. The N-Gain test revealed an average score of 0.6161 (medium category) and an N-Gain percentage of 62%, indicating moderate effectiveness in enhancing creative thinking skills. The study contributes to game-based learning innovation by demonstrating that LUPAS is both feasible and effective in fostering higher-order thinking.